Urgensi Literasi Digital Dalam Meningkatkan Critical Thinking Remaja di Tengah Tantangan Liberalisme (Kajian Surah Al-Jumuah Ayat 2) - Angelica Silfana (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze the digital literacy learning model from the perspective of Surah Al-Jumu'ah verse 2 as an effort to increase adolescents' critical thinking in facing the challenges of liberalism. This research is important because the learning model is an important component in realizing the success of the teaching process. One model that is efficient and easy to apply in the student learning process in class is the digital literacy learning model. The learning development of this digital literacy model supports the escalation of students' critical thinking skills in obtaining information so that teachers can pass on educational values to students. If we analyze the interpretation of Surah An-Nahl verse 2, we will find the true concept of education. The type of method used in this research is library research. To analyze the data we use secondary data which originates from the book of interpretations which explains the interpretation of surah Al-Jum'ah verse 2 and several references from journals related to research. The results of the study show that the digital literacy learning model in surah Al-Jumu'ah verse 2 is the concept of literacy education. Where the word "read to them His verses" shows a literacy learning model then "even though before, they were really in error" shows that literacy is a source that can reduce the challenges of liberalism. With this digital literacy model, it can support adolescents' critical thinking skills in a complex manner which is divided into three, namely critical in analyzing problems, critical in thinking in depth, and critical in evaluating problems. In dealing with ideological liberalism, it is important to know the role of education in reducing its existence with the critical thinking skills of adolescents. From the analysis of surah Al-Jumu'ah verse 2, the urgency of digital literacy can be applied in the learning process to optimize students' critical thinking skills in obtaining concrete information data amidst the challenges of liberalisme.